ESTIMACIÓN DEL COSTO DE GARANTÍA DESCONTADO PARA UN SISTEMA COHERENTE BAJO REPARO MÍNIMO - González, Nelfi Gertrudis; Bueno, Vanderlei (Revista Colombiana de Estadística, 2011)
A martingale estimator for the expected discounted warranty cost process of a minimally repaired coherent system under its component level observation is proposed. Its asymptotic properties are also presented using the Martingale Central Limit Theorem.